Remittances, inclusive finance and governance in selected African countries: empirical insights from the COVID-19 pandemic - Mabrouk, Fatma; Elhaj, Manal (Edelweiss Applied Science and Technology, 2024)
This research intends to explore the effects of inclusive finance on remittances and how these international flows impact economic growth in selected countries from Africa from 1996 to 2020. As per the results of panel dynamics estimation, inclusive finance positively impacts remittances. Furthermore, remittances significantly and positively impact economic growth in countries with solid governance effectiveness. However, they do not affect economic growth in weak governance effectiveness groups. Finally, COVID-19 positively affects remittance receipt, and negatively affects economic growth. Inclusive finance offerings are a crucial transmission channel in receiving remittances to African countries, and governance effectiveness plays a substantial role here.